Enriched microbial consortia from natural environments reveal core groups of microbial taxa able to degrade terephthalate and terphthalamide. - Laura G Schaerer; Sulihat Aloba; Emily Wood; Allison M Olson; Isabel B Valencia; Rebecca G Ong; Stephen M Techtmann (PLoS ONE)
Millions of tons of polyethylene terephthalate (PET) are produced each year, however only ~30% of PET is currently recycled in the United States. Improvement of PET recycling and upcycling practices is an area of ongoing research. One method for PET upcycling is chemical depolymerization (through hydrolysis or aminolysis) into aromatic monomers and subsequent biodegradation. Hydrolysis depolymerizes PET into terephthalate, while aminolysis yields terephthalamide. Aminolysis, which is catalyzed with strong bases, yields products with high osmolality, which is inhibitory to optimal microbial growth. Additionally, terephthalamide, may be antimicrobial and its biodegradability is presently unknown. In this study, microbial communities were enriched from sediments collected from five unique environments to degrade either terephthalate or terephthalamide by performing biweekly transfers to fresh media and substrate. 16S rRNA sequencing was used to identify the dominant taxa in the enrichment cultures which may have terephthalate or terephthalamide-degrading metabolisms and compare them to the control enrichments. The goals of this study are to evaluate (1) how widespread terephthalate and terephthalamide degrading metabolisms are in natural environments, and (2) determine whether terephthalamide is biodegradable and identify microorganisms able to degrade it. The results presented here show that known contaminant-degrading genera were present in all the enriched microbial communities. Additionally, results show that terephthalamide (previously thought to be antimicrobial) was biodegraded by these enriched communities, suggesting that aminolysis may be a viable method for paired chemical and biological upcycling of PET.